Movement-Based Interventions in Pregnancy - Karolina Smolińska; Monika Gajda-Bathelt; Monika Dąbek; Tomasz Antczak; Julia Kulczycka; Zuzanna Perlicka; Weronika Popow; Michał Ciołkosz; Katarzyna Jania; Paulina Sadkowska (Quality in Sport)
Physical activity during pregnancy is established to be a safe and effective strategy to improve maternal and neonatal health. The objective of this article was to investigate the effects of physical activity on the mother, foetus and delivery outcomes. We reviewed literature on physiological adaptations to exercise during pregnancy, maternal and foetal outcomes, and the influence of physical activity on labour duration, mode of delivery, oxytocin administration, perineal trauma, and other perinatal parameters. The findings suggest that regular, moderate physical activity may reduce the risk of gestational complications such as diabetes and hypertension, shorten labour duration, decrease the risk of operative delivery, reduce the need for analgesia and have a beneficial effect on the foetus. Further randomized controlled trials are required to confirm the association between physical activity and pregnancy outcomes, possibly including the differentiation between exercises of various intensity, as well as to provide standardized recommendations.